Logika Dalam Metodologi Ilmiah - Nasution, Andry; Dtm. Mhd. Imam Al-Haq; Marzuki; Nazwa Al-fira Hasibuan (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2025)
This article examines the significant part of rationale in logical strategy, which is essential to the improvement of logical information and understanding. By analyzing different consistent approaches utilized in inquire about, this article distinguishes how deductive and inductive rationale contribute to the legitimacy and unwavering quality of investigation. It too talks about the challenges confronted by analysts in applying suitable rationale in defining speculations and drawing conclusions. Through case considers and down to earth cases, this article illustrates the significance of joining rationale into each step of logical strategy to guarantee the exactness and unwavering quality of logical discoveries. This accentuation on rationale is anticipated to empower more thorough and basic inquiry about over disciplines.